Computational development of the Planar Miniaturized Fast Neutron Detector - Stegeman, Luke (Kansas State University, 2022)
A novel fast neutron spectrometer concept called the Miniaturized Fast Neutron Detector has been computationally developed and characterized via a series of radiation transport simulations. The planar version of the Miniaturized Fast Neutron Detector consists of a plastic converter layer situated in front of an arbitrary number of stacked, electrically isolated thin-silicon diode detectors. Ideally, incoming neutrons impinge upon the plastic, produce recoil ions, and those recoil ions deposit energy in one or more of the diode detectors placed behind the plastic. The spectrometer is capable of reconstructing incident neutron energy spectra without a priori information via at least two distinct unfolding algorithms. The ultimate purpose of the device is to act as an advanced personal dosimeter or area monitor with high position resolution to improve the accuracy of local radiation risk estimates due to secondary neutron radiation. In this work, the device’s ability to unfold three distinct incident neutron energy spectra, the spectroscopic effectiveness of the device as a function of incident integral neutron fluence, and a set of strategies for optimizing and mathematically generalizing the device geometry are all presented. Radiation transport simulations were conducted to generate absorbed dose response functions for each diode detector and to compute the absorbed dose in each diode detector due to incident ²⁵²Cf, AmB, and AmBe neutron energy spectra as a function of integral neutron fluence. These data are used to test the unfolding capability of the device and characterize its spectroscopic effectiveness. Two unfolding algorithms are considered: the matrix inversion unfolding method, which employs a non-negative least-squares algorithm, and the SPUNIT method. Further radiation transport simulations and analyses were conducted to develop a strategy to optimize the dimensions of the plastic conversion layer and the diode detectors for any arbitrary neutron energy range so that individual device iterations can be tailored to various environments. The results of this work demonstrate that the planar Miniaturized Fast Neutron Detector is capable of unfolding a diverse range of incident neutron energy spectra without a priori information. The effectiveness of the device is quantified as a function of integral neutron fluence and this quantity can be used to determine the minimum integral neutron fluence necessary to generate acceptable unfolded neutron energy spectra (and, by extension, dosimetric quantities and risk-related metrics). The results also demonstrate that the efficiency and energy discrimination capabilities of the current iteration of the device (one with 20 stacked diode detectors) can be improved by decreasing the thickness of the plastic conversion block and increasing the number of uniformly sized diode detectors (or gradually increasing the thickness of diode detectors as a function of device depth).
Keywords: Fast neutron spectrometer; Semiconductor; Dosimetry; Miniature neutron spectrometer; Neutron spectrum unfolding